Femtosecond optical tomograthy - Курський, Ю. С.; Кальна, О. О. (ХНУРЕ, 2020)
The aim of the work is development of medical optical tomography technologies. The physical principles, tasks, and boundary possibilities of the optical tomography systems are considered. The autors propose to use the femtosecond lasers, operating in the «optical comb» mode, as a lught source in optical tomography system. The advantages of this source uses were analyzed and resolution power of femtosecond optical tomographs was calculated in the artical.
Keywords: medical optical tomography technologies